2009
DOI: 10.1016/j.ress.2008.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Global sensitivity analysis of computer models with functional inputs

Abstract: Global sensitivity analysis is used to quantify the influence of uncertain input parameters on the response variability of a numerical model. The common quantitative methods are appropriate with computer codes having scalar input variables. This paper aims at illustrating different variance-based sensitivity analysis techniques, based on the so-called Sobol's indices, when some input variables are functional, such as stochastic processes or random spatial fields. In this work, we focus on large cpu time comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 27 publications
1
33
0
Order By: Relevance
“…Hence, var(ε)/var(y) is the so-called "total sensitivity index" with respect to the non-important factors, denoted S Tv (Homma et Saltelli [7]). Here, the non-important factors v are considered as noise in the model, and the index S Tv is a measure of this noise over the response y (as in Iooss and Ribatet [8]). A low value confirms that the dropped factors are really non-important.…”
Section: The Screening Methodsmentioning
confidence: 99%
“…Hence, var(ε)/var(y) is the so-called "total sensitivity index" with respect to the non-important factors, denoted S Tv (Homma et Saltelli [7]). Here, the non-important factors v are considered as noise in the model, and the index S Tv is a measure of this noise over the response y (as in Iooss and Ribatet [8]). A low value confirms that the dropped factors are really non-important.…”
Section: The Screening Methodsmentioning
confidence: 99%
“…Some authors have suggested solutions to handle spatially distributed inputs as well (Volkova et al, 2008 ;Iooss & Ribatet, 2009;Ruffo et al, 2006;Lilburne & Tarantola, 2009). We describe in this section how to estimate sensitivity indices in model M by associating randomly generated realizations of uncertain 2D-field Z(u) to scalar values, according to the approach developed by Lilburne and Tarantola.…”
Section: Estimating Sensitivity Indices Using Geostatistical Simulationsmentioning
confidence: 99%
“…Assum-ing that the model output is a Gaussian field trajectory, recent studies [11,12,13,14] build two independent or joint deterministic metamodels to fit the mean and the covariance of the assumed Gaussian process. Also based on the joint metamodeling approach, [15] simultaneously surrogates the mean and the dispersion using two interlinked Generalized Additive Models. Alternatively, the study carried out in [16] focused on projecting the output density on a basis of chosen probability density functions.…”
Section: Introductionmentioning
confidence: 99%